PENGARUH LAND APPLICATION TERHADAP JUMLAH PRODUKSI BUAH KELAPA SAWIT DI PT. CITRA PUTRA KEBUN ASRI JORONG ESTATE - Iswahyudi, Herry; Safitri, Maharani; ukmana, Mila L; Indriani, Indriani (EnviroScienteae, 2024)
This study aims to describe the impact of utilizing palm oil mill effluent on the amount of palm oil fruit production through land application at PT. CPKA. The research was conducted using a quantitative analysis method with a descriptive approach. Data collection techniques used in this study include observation, interviews, literature review, and documentation. PT. CPKA is a palm oil industry engaged in palm oil plantation and processing. According to the Directorate General of Processing and Marketing of Agricultural Products (PPHP) (2006), each ton of fresh fruit bunches (FFB) has the potential to produce liquid waste amounting to 50% of the total waste generated. PT. CPKA processes waste using a wastewater treatment plant (WWTP) system, which is then utilized as fertilizer for application on plantation land (land application). The research results show that palm oil mill effluent at PT. CPKA has a positive impact on the increase in palm oil production, with yields of 16.73 tons/ha in 2015, 11.79 tons/ha in 2016, 18.65 tons/ha in 2017, 29.46 tons/ha in 2018, and 26.26 tons/ha in 2019. These figures are higher compared to the production of palm oil without the application of palm oil mill effluent, which were 15.67 tons/ha in 2015, 10.38 tons/ha in 2016, 15.72 tons/ha in 2017, 25.92 tons/ha in 2018, and 25.11 tons/ha in 2019.